DETERMINANTS OF PROFITABILITY OF SHARIA PEOPLE'S FINANCING BANKS IN INDONESIA - Sakinah Sakinah; Irene Rini Demi Pangestuti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The success of banking is reflected in its profitability, which is the result of all the activities and operations of banking companies that have been running. Financial reports can provide an overview of the level of profitability achieved by banking companies. This study aims to test howthe influence of CAR, liquidity, efficiency, credit risk, and bank size on the profitability of Islamic People's Financing Banks (BPRS) registered with OJK duringperiod 2018-2021. The research method is quantitative with secondary data. PSample determination was carried out using a purposive sampling method, the research sample criteria were (a) BPRS registered with the OJK, (b) BPRS that had a complete report for 2018 - 2021 and sent it to the regulator (OJK) and a positive ROA.The research analysis tool uses Eviews with the methodselection is the Random Effect Model (REM). The research results show that BOPO, credit risk, bank size and Covid control have a negative effect on profitability, while CAR and FDR have no effect. In the f-test the feasibility of the panel data equation model, the sig value. 0.000 meansCAR, FDR, BOPO, NPF and Assets as well as the Covid control variable together have a significant effect on the profitability variable. Determination test resultsRÂ² of0.856862, meaning that ROA is influenced by the variables CAR, FDR, BOPO, NPF, and Assets as well as the covid control variable of 85.69%, while the remaining 14.31% is influenced by other factors outside of these variables.